Ambientes cársticos em Sergipe: vulnerabilidade e instrumentos para sua gestão - Macedo, Heleno dos Santos (2019)
The process of land use and occupation in karstic landscapes has occurred in a disorderly way in all places. In Sergipe, this situation is putting the karstic landscapes in threat. The karstic landscapes taken in research, refers to the Karst Traditional Sergipe Basin, located in the Coastal Province and Traditional Continental Margin and Karst Olhos d'Água/ Frei Paulo, inserted in the range of sergipe vaza-barris folds in the field. The method of analysis for foundations of research, based on the general theory of systems, with a bias in the approaches of chaos theory of Complex dynamical systems and fractal geometry. This study, outlined as general objective to analyze the karstic environments in Sergipe, emphasizing the natural and environmental vulnerability for purposes of proposals for planning and management. Thus, for compliance with this and other specific goals, adopted different methodological procedures, associated with the various stages, prioritizing, therefore, the literature review, the cartographical survey and field work. Among other results, it was found that the karstic environments in Sergipe feature incipient developments, due to factors related to the size of the Package, type of lithology, absence of rocks with secondary porosity due to the lack of tectonic activation, low gradient of the topography, climate, and especially by the metamorphism of carbonates in the Karst Olhos d'Água/Frei Paulo o and coverage of the carbonatic rocks in the Karst Sergipe Basin by the Barreiras Group. In spite of the exocarste champions, it was observed that constitutes by features of lapiás, sinkholes, blind valleys and plains of dissolution (poljés), while the endocarste is composed by 171 autogênicas cavities and with low horizontal development, located mostly in the Karst Olhos d'Água/ Frei Paulo. In what refers to the use and occupation of the soil, it is highlighted the presence of mining of limestone for cement production and corrective for soil, the practice of grazing and agriculture, mainly in the Karst Sergipe Basin. The natural and environmental vulnerability of Karst Sergipe Basin is high, due to the inadequacy of land use and occupation of the soil. The Karst Olhos D'Água/ Frei Paulo o finds itself in a situation of natural and environmental vulnerability very high, due to factors associated with intensive use for grazing causing the withdrawal of vegetation and accelerating its degradation. In the final reasons, stresses that in the karstic areas, there is urgent need for preventive and mitigating measures. Hence the proposition of Environmental Zoning for the karst, with Division into five zones, namely: Areas of possible use for agriculture (ZUPA); zones of protection of KARSTIC Landscapes (ZPPC); Conservation zones of the karstic Landscapes (ZCPC); conservation zones and Urban Development (ZCDU) and areas of use for mining and industry (ZUMI). In addition, became also the proposition of the insertion of measures for the conservation of karst in Master Plans and creation of two areas of environmental protection: APA Taquari Maruim, in the Karst Sergipe Basin and APA Olhos D'Água, in the Karst Olhos D'água/Frei Paulo.